Hadron Physics - Bressani, T (IOS Press, 2013)
The CLVIII Course “Hadron Physics” of the Enrico Fermi School, held in Varenna from June 22 to July 2, 2004, was almost entirely dedicated to Hypernuclear Physics and Antiproton Physics